Acute effects of training on hurdle configuration during sprint hurdle motion - Shibayama, K.; Fujii, N.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Here we assessed the acute effects of training in hurdle configuration on sprint hurdle motion in five male hurdlers. We compared the hurdlers` motion between the pre- and post-training conditions for three different types of training programs. Our results showed that a short-interval training program was effective in reducing the duration of all four step, particularly that of the 2nd step. On the other hand, a long-interval training program particularly influenced the characteristics of the 3rd step without improving the overall four steps. Thus, a long-approach training was effective in adjusting the ground reaction force in the support phase of the 4th step, necessary to appropriately clear the hurdle.